Forage seed business and scaling - Gebreyes, Million; Bezabih, Melkamu; Assefa, Getnet; Adie, Aberra; Mekonnen, Kindu; Mesfin, Hailemariam (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation in Media Training Workshop on Climate Smart Feed and Forage Innovations. Addis Ababa, Ethiopia.